CD8+ lineage dendritic cells determine adaptive immune responses to inflammasome activation upon sterile skin injury. Issue 1 (6th December 2017) - Chakraborty, Rituparna; Chandra, Janin; Cui, Shuai; Tolley, Lynn; Cooper, Matthew A.; Kendall, Mark; Frazer, Ian H.
Abstract: The molecular links between sterile inflammation and induction of adaptive immunity have not been fully identified. Here, we examine how damage‐associated molecular patterns (DAMPs), as opposed to pathogen‐associated molecules (PAMPs), regulate the immune response to non–self‐antigens presented at the site of a physical injury. Heat applied briefly to the skin invokes sterile inflammation, characterized by local cell death and caspase‐1 activation without demonstrably disrupting skin integrity. Co‐delivery of ovalbumin (OVA) with heat injury induces OVA‐specific CD8 + T‐cell responses, and this is dependent on caspase‐1 activation and MyD88 signalling. Using Id2flox/flox‐CD11cCre+ mice, we demonstrate that CD8 + lineage DCs are required to induce OVA‐specific CD8 + T‐cell responses following heat injury. Consistent with this observation, intradermal administration of CD8 + lineage DCs but not CD11b + lineage DCs restores priming of CD8 + T‐cell responses in Casp‐1 −/− mice. Thus, we conclude that a sterile injury induces CD8 + T‐cell immune responses to local antigen through caspase‐1 activation and requires CD8 + lineage DCs, a finding of significance for immunotherapy and for the pathogenesis of autoimmunity.